Wordplay on Malangan T-shirt: A Linguistic Resource for Language Education - A. Gusti Efendy (Juliet, 2024)
This study investigates the linguistic features of wordplay found on Malangan T-shirts within the framework of language, culture, and pedagogy. By analyzing a corpus of Malangan T-shirt designs, the research identifies a variety of wordplay types, including malapropism, ambiguity, and jargon, offering rich opportunities for language exploration. The study contributes to the understanding of the relationship between language, culture, and visual communication, while also highlighting the potential of Malangan T-shirt wordplay as a valuable resource for enhancing language education and fostering cultural awareness.